Peritoneoectomy and the multiorgan resection in prevalent tumors of abdominal cavity and small pelvis - O. I. Тkachenko; O. V. Bondar; S. G. Chetverikov; V. E. Maksymovskyi; M. S. Chetverikov; V. V. Chetverikova–Ovchynnyk (Клінічна хірургія, 2021)
Objective. To estimate the results of peritoneoectomy and multiorgan resection in the treatment of prevalent tumors of abdominal cavity and small pelvis.